2017
DOI: 10.1097/ccm.0000000000002091
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of High-Flow Nasal Cannula Oxygen Therapy on Mortality and Intubation Rate in Acute Respiratory Failure: A Systematic Review and Meta-Analysis

Abstract: No difference in mortality or intubation was detected in patients with acute respiratory failure treated with high-flow nasal cannulae compared with usual care. High-flow nasal cannulae seem well tolerated by patients. Further large randomized controlled trials are required to evaluate their utility in this setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
1
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(81 citation statements)
references
References 47 publications
3
70
1
7
Order By: Relevance
“…In the first study, no differences in terms of mortality or higher respiratory support requirement was observed [26]. Most recently, Monro-Somerville et al [27] found that, although HFNC appears to be well tolerated, no difference in intubation rates or mortality was observed in patients treated with HFNC compared to those treated with usual care (conventional oxygen or NIV). However, the required information size was not reached: in fact, only 30.6 and 62.3% of the estimated needed patients were included for the primary (mortality) and secondary (intubation) outcomes, respectively.…”
Section: Effects On Intubation Rate and Mortalitymentioning
confidence: 99%
See 1 more Smart Citation
“…In the first study, no differences in terms of mortality or higher respiratory support requirement was observed [26]. Most recently, Monro-Somerville et al [27] found that, although HFNC appears to be well tolerated, no difference in intubation rates or mortality was observed in patients treated with HFNC compared to those treated with usual care (conventional oxygen or NIV). However, the required information size was not reached: in fact, only 30.6 and 62.3% of the estimated needed patients were included for the primary (mortality) and secondary (intubation) outcomes, respectively.…”
Section: Effects On Intubation Rate and Mortalitymentioning
confidence: 99%
“…Two recent systematic reviews and meta-analyses have also been published that evaluated the effectiveness of HFNC [26,27]. In the first study, no differences in terms of mortality or higher respiratory support requirement was observed [26].…”
Section: Effects On Intubation Rate and Mortalitymentioning
confidence: 99%
“…Bis heute konnten mehrfach die Vorteile der NHF-Sauersto therapie im Vergleich zur konventionellen Sauersto therapie [1] oder nicht invasiven Ventilationstherapie [2] bei Patienten mit hypoxämischer Atmungsinsu zienz gezeigt werden. Die positiven E ekte beruhen teilweise darauf, dass eine höhere Sauersto konzentration appliziert werden kann, auf einer verbesserten mukoziliären Clearance durch die Anwärmung der Atemluft [3] und auf dem Aufbau eines positiven Atemwegsdruckes bei gleichzeitiger Senkung des Totraums [4] durch den hohen Gasuss.…”
Section: High-flow-sauerstoff Als Option Bei Maskenintoleranzunclassified
“…Among patients with acute hypoxemic respiratory failure, the use of HFNC is associated with rates of intubation and death equivalent to rates with commonly used conventional oxygen therapy and noninvasive positive pressure ventilation (NPPV) [1][2][3]. In addition, HFNC has characteristics that greatly contribute to maintaining a better quality of life (QOL), such as allowing oral intake, oral care, and conversation.…”
Section: Introductionmentioning
confidence: 99%